Migrant Workers and Higher Education: Paradoxes of Democratization of Higher Education - Muna Yastuti Madrah; Ahmad Muflihin; Warsiyah Warsiyah (Jurnal Empirika, 2021)
Migrant Workers and Higher Education issues seem two different contradictory topics. Many research on migrant workers often associates them with pragmatical activities, the working class, and marginal groups. On the other hand, Higher Education (HE) is more often associated with idealistic spaces, middle classes, and academics environment. This paper presents the phenomenon of Indonesian migrant worker-students in South Korea. We found the increasing number of Indonesian migrant workers who pursue higher education through overseas Indonesian Open University (Universitas Terbuka) in Korea and ICT-based Korean local universities. We examine how migrant workers take advantage of the transformation of higher education. We try to answer whether higher education experienced democratization will reduce social inequality, or on the contrary, it will be trapped in an educational capitalization that sharpens the gap.